Left acute neovascular glaucoma after right carotid endarterectomy - Matija Radojcic, BBiomedSc, BSc(Hons), MD, PGDipSurgAnat; Robin Abell, MBBS(Hons), MMed; Jason Chuen, MBBS, PGDipSurgAnat, FRACS(Vasc), MPH (Journal of Vascular Surgery Cases and Innovative Techniques, 2018)
Carotid endarterectomy is a commonly performed vascular surgical procedure with well-known complications, such as stroke and nerve injury. Neovascular glaucoma (NVG) is an exceedingly rare complication after carotid endarterectomy that can result in loss of vision. All previous reports of NVG after carotid endarterectomy have occurred on the same side as the carotid surgery; in this report, we present a case of left-sided NVG after right carotid endarterectomy for contralateral ocular ischemic syndrome. We aim to emphasize the importance of early recognition and treatment of this serious complication as rapid intervention has the potential to save sight.